Implementasi Metode Dempster-Shafer untuk Mendiagnosa Penyakit Tanaman Padi - Syailendra Orthega; Nurul Hidayat; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The rice plant disease often resulting in growth of rice plant becomes compromised, and make the rice production to fail. The incidence of disease on rice comes from bacteria, fungi, viruses, and other than that of nutrient deficiencies also include diseases. Diseases of the plants also have a major influence on growth. Diseased plant growth is usually disturbed, changed into a dwarf and some leaf are changing color, for example, the leaves turn yellow, or dry out. In research this time, the system was developed using Dempster-Shafer method as rice plant disease diagnosis.The collection of data in this study using a study literature, interview and observation methods.The results of this research is a system to diagnose diseases of the rice plant using Demspter-Shafer method that includes a variety of symptoms, causes, solutions and results of diagnosis the based of knowledge of experts or experts in the field of agriculture. Of the test case that have been conducted, the results of testing the accuracy of 90% indicating that the application is functioning properly in accordance with the method of Dempster-Shafer